Characterisation and Modelling of Continuous-Discontinuous Sheet Moulding Compound Composites for Structural Applications - Trauth, Anna (Schriften des Instituts fur Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut fur Technologie, 2020)
The main objective of this work is to significantly deepen the understanding of the material and the structural behaviour of continuous-discontinuous SMC composites, following a holistic approach to investigate microscopic aspects, macroscopic mechanical behaviour as well as failure evolution at the coupon, structure and component level. In addition, criteria to evaluate the effect of hybridisation are introduced and modelling approaches are presented and discussed.